Cellulose nanofibers from oil palm mesocarp fiber and their utilization as reinforcement material in low density polyethylene composites - Tengku Yasim Anuar, Tengku Arisyah (2018)
Oil palm mesocarp fiber (OPMF) is made up of mainly cellulose, making it a potentially raw material for microfibrillated cellulose (MFC) and cellulose nanofiber (CNF) production. MFC and CNF properties may be influenced by their production method; it is therefore in this study three different methods were used for the production of MFC and CNF from OPMF: electrospinning, ultrasonication and high pressure homogenization. In electrospinning, cellulose concentration and ionic liquid formulation affected the cellulose solubility, and viscosity; which influenced the properties of the MFC produced. The best MFC was formed when 6% (w/v) OPMF-cellulose was dissolved in ([EMIM]Cl:([C10MIM][Cl]):DMF; whereby MFC with average diameter of 200 to 500 nm, crystallinity of 57% and Td50% at 348 °C was obtained. By using electrospinning, nano-sized fiber (< 100nm) was not obtained, hence, ultrasonication and high pressure homogenization were conducted. Ultrasonication at 125 W and 36 kHz for 9 hours produced mixture of MFC and CNF with non-homogeneous diameter size between 40 – 200 nm, having crystallinity index and Td50% of 41% and 338 C, respectively. Meanwhile, high pressure homogenizationconducted at 50 MPa for 30 passes with cellulose concentration of 0.2% (w/v) resulted in CNF with diameter of 80 – 100 nm, crystallinity index of 62% and Td50% at 353 C. The CNF obtained from high pressure homogenization method was then used as reinforcement material for low density polyethylene (LDPE) composites production. Effect of melt compounding methods on the mechanical properties of nano-sized fiber composites was determined. Composites consisted of low density polyethylene (LDPE), maleic anhydride-grafted PE (PEgMA) and CNF at formulations of 97/3/0.5–5 (wt/wt/wt), respectively, were prepared by twin screw extrusion and internal melt blending processes. Morphology of the composites as revealed by SEM-EDS and X-CT scan showed that the twin screw extrusion process permitted homogeneous dispersion of CNF, thus led to an increment of up to 195% in flexural strength compared to neat LDPE. In contrast, the composites prepared by internal meltblending method showed an agglomeration and heterogeneous dispersion of CNF within LDPE matrix, caused the composites to have lower tensile strength and flexural strength compared to those prepared by twin screw extrusion. CNF-based composites preparation method can be shortened by introducing simultaneous nanofibrillation and melt compounding using one unit operation. Herewith, a onepot process was conducted by using an extruder with specially designed twin screw. FE-SEM micrograph exhibited that the resultant LDPE/CNF composites had CNF with average diameter of 80 – 100 nm. These composites prepared by one-pot process had similar properties with those prepared in conventional twopot process, with the advantage of having higher productivity – by almost doubled. A two-step in one unit operation (2-in-1) would be an ideal process for composites making as this method may improve productivity, reduce downtime in between the two steps, could contribute to a lower capital and processing costs, and may have lower energy consumption. The one-pot process also meets most of the Green Chemistry Principles; suggesting the method as a sustainable and greener method for polymer composites production.